The Anastomotic Angle of Hemodialysis Arteriovenous Fistula Is Associated With Flow Disturbance at the Venous Stenosis Location on Angiography - Yang, Chih-Yu; Li, Ming-Chia; Lan, Chien-Wen; Lee, Wang-Jiun; Lee, Chen-Ju; Wu, Cheng-Hsueh; Tang, Jing-Min; Niu, Yang-Yao; Lin, Yao-Ping; Shiu, Yan-Ting; Cheung, Alfred K.; Lee, Yan-Hwa Wu; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
The juxta-anastomotic stenosis of an arteriovenous fistula (AVF) is a significant clinical problem in hemodialysis patients with no effective treatment. Previous studies of AV anastomotic angles on hemodynamics and vascular wall injury were based on computational fluid dynamics (CFD) simulations using standardized AVF geometry, not the real-world patient images. The present study is the first CFD study to use angiographic images with patient-specific outcome information, i.e., the exact location of the AVF stenotic lesion. We conducted the CFD analysis utilizing patient-specific AVF geometric models to investigate hemodynamic parameters at different locations of an AVF, and the association between hemodynamic parameters and the anastomotic angle, particularly at the stenotic location. We analyzed 27 patients who used radio-cephalic AVF for hemodialysis and received an angiographic examination for juxta-anastomotic stenosis. The three-dimensional geometrical model of each patient's AVF was built using the angiographic images, in which the shape and the anastomotic angle of the AVF were depicted. CFD simulations of AVF hemodynamics were conducted to obtain blood flow parameters at different locations of an AVF. We found that at the location of the stenotic lesion, the AV angle was significantly correlated with access flow disturbance (r = 0.739; p < 0.001) and flow velocity (r = 0.563; p = 0.002). Furthermore, the receiver operating characteristic (ROC) curve analysis revealed that the AV angle determines the lesion's flow disturbance with a high area under the curve value of 0.878. The ROC analysis also identified a cut-off value of the AV angle as 46.5, above or below which the access flow disturbance was significantly different. By applying CFD analysis to real-world patient images, the present study provides evidence that an anastomotic angle wider than 46.5 might lead to disturbed flow generation, demonstrating a reference angle to adopt during the anastomosis surgery.